SOCIAL DISTANCING MOBILE APPLICATION FOR VISUALLY IMPAIRED PEOPLE - AMRAN, NIK NISA SORFIA (IRC, 2020)
The use of mobile applications is becoming very popular nowadays and it has become a necessity for everyone even people who are having sighted disabilities are using mobile application to ease daily routine / life. Early year of 2020, outbreak of Covid-19 had happened and people was totally relying on smartphones and mobile application during this New Norma. Also, there are also applications that have been specially developed for Covid-19 purpose. However, mobile application for social distancing are not given priority, especially for sighted disabilities that needs the application to protect themselves from the infection. Social distance rules can be difficult to follow by the visually impaired people and they are facing the challenge to keep their distance of 1-2 meters between other people due to Covid-19. Hence, the main objective of this project is to discover the type of features that give better facilities for visually impaired people to use the application. The application will provide social distancing detector that will detect the distance of 1-2 meters of the user with object (people). The research will cover some of the mobile application for Covid-19 purpose, social distancing and also features to develop mobile application for visually impaired people.